2018
DOI: 10.26710/jafee.v4i2.523
|View full text |Cite
|
Sign up to set email alerts
|

Equity Liquidity and Firm Investment: Evidence from Pakistan

Abstract: This paper examines how equity liquidity affects firms’ investment decisions. We use an unbalanced panel data for a sample of 360 non-financial firms of Pakistan for the period 2001-2016. We apply the Hausman specification test to identify whether fixed or random effects model is appropriate. Using two alternative measures of equity liquidity, we find that equity liquidity has a significant positive impact on firms’ investment decisions. We also show that several firm-specific factors are significant in determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…According to researchers, blockholders reduce information asymmetry and impact positively on long-term financial performance (Florackis & Ozkan, 2009;Pawlina & Renneboog, 2005). Claessens et al (1997); Rashid (2011) study on 706 Czech Republic firms from 1992 to 1993 show that ownership of a blockholder enhances firm performance.…”
Section: Blockholder Ownershipmentioning
confidence: 99%
“…According to researchers, blockholders reduce information asymmetry and impact positively on long-term financial performance (Florackis & Ozkan, 2009;Pawlina & Renneboog, 2005). Claessens et al (1997); Rashid (2011) study on 706 Czech Republic firms from 1992 to 1993 show that ownership of a blockholder enhances firm performance.…”
Section: Blockholder Ownershipmentioning
confidence: 99%
“…It means that liquidity positively affects investment decisions in fixed assets. Research conducted by Sajid et al (2016), Hartono and Wahyuni (2005), and Rashid and Karim (2018) uncovered that liquidity positively affected investment decisions. However, Kalusová and Badura (2022) found that liquidity negatively influenced investment determination.…”
Section: H2: Solvency Negatively Affects Fixed-asset Investment Decis...mentioning
confidence: 99%
“…Companies with high liquidity can invest more in capital expenditures, fixed assets such as land or property, production machine, buildings, engine, and equipment. According to Hartono and Wahyuni (2005), and Rashid and Karim (2018), liquidity positively affected investment decisions, whereas research by Yunita and Yuniningsih (2020) found that liquidity had a negative effect on investment decisions.…”
Section: H2: Solvency Negatively Affects Fixed-asset Investment Decis...mentioning
confidence: 99%